Socio-Economic Determinants of Household Expenditure: An Analysis of Rural and Urban Nagpur (Journal of Informatics Education and Research, 2024)
This study explores the socio-economic determinants of household expenditure patterns in the Nagpur district, focusing on three key categories: food, health, and non-food (excluding health). Using regression analysis, the study examines the influence of variables such as adjusted total income, age, gender, education, occupation, and household size on spending behaviors. The findings reveal significant variation in the determinants across rural and urban areas. For urban households, income, education, and household size are significant predictors of food and non-food expenditure, while health expenditure remains predominantly influenced by income. In rural households, household size and education play a stronger role in shaping food expenditure, while health spending is significantly associated with age and gender. The study provides insights into the underlying socio-economic drivers of consumption behavior and offers policy recommendations aimed at improving household welfare and addressing regional disparities.